ANALYSIS OF STUDENTS' METACOGNITION IN SOLVING MATHEMATICAL PROBLEMS ON THE TOPIC OF SYSTEMS OF LINEAR EQUATIONS WITH TWO VARIABLES BASED ON THE INITIAL ABILITY OF GRADE VIII STUDENTS OF SMPN 18 MAKASSAR - Vinola, Cindy Ria; Arsyad, Nurdin; Takdirmin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2025)
The main purpose of this study is to analyze students' metacognition in solving mathematical problems on the subject of a two-variable linear equation system based on students' initial abilities. This type of research is a descriptive study with a qualitative approach which was carried out at SMP Negeri 18 Makassar. The subjects of this study consisted of 3 people who were taken each by 1 student with low ability, medium ability, and high ability. Data collection techniques used test and interview methods, and instrument validation was carried out with 2 expert validation stages. Technical analysis of data using descriptive analysis and qualitative data analysis starting from data reduction, data presentation and drawing conclusions. Test the validity of the data using triangulation techniques. From the results of the study it was concluded that (1) the subject of high initial ability category could fulfill all metacognitive indicators, namely prediction, planning, monitoring, and evaluation (2) the subject of medium initial ability category was only able to fulfill two metacognitive indicators of the four metacognitive indicators, namely prediction and planning, (3) the subject of low initial ability could only fulfill one metacognitive indicator of the four metacognitive indicators, namely predictions of students being able to understand what is known and asked in the questions, students are also able to change story questions into mathematical models.